Building Language, Literacy, Numeracy, and Digital Skills with Aboriginal Rangers in the Northern Territory - Page, Jaemie (Australian and International Journal of Rural Education, 2024)
Ranger programs across North Australia are a success story, providing important environmental, social and cultural services that help people get back out on their Country to do vital work, such as carbon abatement fire programs, weed and feral animal management, cultural site maintenance, and Learning on Country programs for youth. Many rangers struggle with the English language, literacy, numeracy and digital skills needed to participate effectively in work and training. The Batchelor Institute Conservation and Land Management team have developed effective language, literacy, numeracy and digital skills programs through Foundation Skills Training being delivered across the Northern Territory top end and recently Uluru. With extensive knowledge and experience in ranger work, trainers can develop and adapt language, literacy, numeracy and digital skills programs that are contextualised to the work of rangers and meet their needs as well as those of their host organisations. Secure, targeted funding can provide long-term support to further develop these programs and better prepare and support learners with training and work. This document outlines existing work and how it can be expanded across the region.